2012
DOI: 10.1111/j.1440-1681.2011.05644.x
|View full text |Cite
|
Sign up to set email alerts
|

Vagal nerve modulation: A promising new therapeutic approach for cardiovascular diseases

Abstract: The physiological activities of the mammalian heart are regulated by the autonomic nervous system. An imbalanced autonomic nervous system with increased sympathetic tone and reduced vagal tone has been implicated in cardiovascular diseases. Experimental and clinical reports have demonstrated that vagal nerve activation is able to improve outcomes for multiple cardiovascular diseases, such as ischaemic heart disease, heart failure, arrhythmia and hypertension. In this paper, we mainly focus on the potential car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(15 citation statements)
references
References 51 publications
1
14
0
Order By: Relevance
“…Previous studies have demonstrated that vagal activation is capable of exerting cardioprotective effects in various cardiovascular diseases, including ischemic heart disease, heart failure, arrhythmia and hypertension (7,15). In the present study, VS was initiated at 15 min following acute myocardial ischemia and maintained for 30 min, which is similar to a previous study (9).…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Previous studies have demonstrated that vagal activation is capable of exerting cardioprotective effects in various cardiovascular diseases, including ischemic heart disease, heart failure, arrhythmia and hypertension (7,15). In the present study, VS was initiated at 15 min following acute myocardial ischemia and maintained for 30 min, which is similar to a previous study (9).…”
Section: Discussionsupporting
confidence: 63%
“…Previous studies have demonstrated that vagal stimulation (VS) and acetylcholine (ACh) are capable of exerting cardioprotective effects in various cardiovascular diseases (7,8). Furthermore, the inhibition of inflammation has been demonstrated to be one of the major pathophysiological mechanisms by which VS induces cardioprotection (9,10).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, the importance of elevating vagal activity has been discussed. [7][8][9]26 A growing body of evidence indicates that the vagal nerve and its neurotransmitter acetylcholine play defensive roles in the pathogenesis of cardiovascular diseases 27 ; however, few studies have explored the effects of acetylcholine treatment on Ca 2+ regulation in endothelial cells in the context of I/R. Importantly, this study demonstrated that acetylcholine reduced both mitochondrial and cytosolic Ca 2+ overload that inhibiting the Ca 2+ -related apoptotic pathway, leading to attenuation of cell death and preservation of endothelial structure.…”
Section: Discussionmentioning
confidence: 99%
“…Increased vagal activity reduces cardiovascular risk factors and improves prognosis [17,18,19]. Recently, vagal nerve stimulation (VNS) has been used as a promising therapeutic approach for chronic heart failure [20,21,22].…”
Section: Introductionmentioning
confidence: 99%